Peran Strategi Manajemen Sumber Daya Manusia Dalam Meningkatkan Produktifitas Kerja Karyawan - Siska Asriyanti; Ayu Arum Febrianti; Fitri Nur Wulansari; Syahrul Mubarok; M. Isa Anshori (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this article is to explain the role of effective human resource management strategies in increasing employee work productivity. This article focuses on the role of HRM in business organizations and how HRM strategies can help organizations increase employee work productivity. This research was carried out using the literature study method, namely by analyzing and examining in depth the literature related to the research topic, including previous research. The main source for this research is literature that is closely related to the literature review, including books on research methods, scientific papers, online sources, and other relevant publications. The following are several important roles of human resource management strategies in increasing employee work productivity: human resource planning, effective recruitment and selection, employee development, effective performance management, providing compensation and rewards, conflict management and employee welfare, effective communication open and clear. In order to create innovation that can improve the company's competitiveness and quality, developing and improving employee performance must be a top priority for the company. The factor that a company must prioritize is the employee performance factor. To achieve the goals of a company, it is necessary to implement effective HR management strategies to increase employee work productivity.